Strategic Issues Management and Organizational Outcomes - Pursey P.M.A.R. Heugens (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2003)
This paper assesses whether strategic issues management activities contribute anything worthwhile to corporate performance by reporting two studies on the issues management strategies of Dutch food firms during the recent introduction of genetically modified ingredients. The first study applied grounded theory methods to assess which issues management activities were used most prominently by industry incumbents. The results indicated that in the present setting companies most significantly relied on stakeholder integration techniques and capability development. The second study used survey data to link these activities to a broad array of organizational outcome variables. The data showed that the adoption of issues management activities positively influenced firm competitiveness as well the relative standing of firms amongst their peers.
Keywords: 330; issues management; stakeholder integration; capability development; competitive advantage; corporate reputation